Cross cultural awareness and social justice in counseling - Ellis, Cyrus Marcellus; Carlson, Jon (Routledge, 2009)
"Many societal and cultural changes have taken place over the past several decades, almost all of which have had a significant effect on the mental health professions. Clinicians find themselves encountering clients from highly diverse backgrounds more and more often, increasing the need for a knowledge of cross-cultural competencies. Ellis and Carlson have brought together some of the leaders in the field of multicultural counseling to create a text for mental health professionals that not only addresses diversity but also emphasizes the counselor's role as an advocate of social justice. The theoretical foundation for this book rests on research into diversity, spirituality, religion, and color-specific issues. Each chapter addresses the unique needs and relevant issues in working with a specific population, such as women, men, African Americans, Asian Americans, Spanish-speaking clients, North America's indigenous peoples, members of the LGBT community, new citizens, and the poor, underserved, and underrepresented. Issues that enter into the counselor-patient relationship are discussed in detail for all of these groups, with the hope that this will lead to a greater understanding and sensitivity on the part of the counselor for their patients. This is an important and timely book for both counselors-in-training and those already established as professionals in today's highly diverse and constantly-changing society."--Jacket.